Energy consumption and carbon emissions of mixing plant in asphalt pavement construction with a case study in China and reduction measures - Yixuan Liu; Jun Yang; Houzhi Wang; Shinan Liu; Yulou Fan; Yixin Zhou; Minghui Gong; Wei Huang (Case Studies in Construction Materials)
The asphalt pavement construction consumes a lot of energy and produces greenhouse gas emissions. The production and transportation of asphalt mixture in the mixing plant is an important process. In this paper, the energy consumption and carbon emission model in the material production and transportation stage are established. A mixing plant in Southeast China is taken as a case to analyze the energy consumption and carbon emission. The influencing factors are analyzed from three aspects: external environmental conditions, energy structure and material type. Through aggregate water content test and water loss behavior test, the influences of environmental temperature and humidity, initial and heating temperature, aggregate lithology and particle size on aggregate water content and water loss law were analyzed. The energy consumption and carbon emission under different environmental conditions were calculated. When the mixing temperature was 160°C, the energy consumption generated by water accounted for 20.23 % of the total and the CO2e percentage was 18.61 % as the aggregate water loss increased. At different initial and final temperatures, the percentage of energy consumption generated by water in the total energy consumption was in the order of basalt > reclaimed asphalt pavement (RAP) material > diabase > limestone. From the perspective of using natural gas, solar energy and hydrogen energy, the feasibility of popularizing clean energy in production and transport is analyzed. The carbon emissions of ordinary asphalt mix (AC), stone mastic asphalt mixture (SMA) and hot-mixed epoxy asphalt concrete (EA) were analyzed. The CO2e of each ton of mixture is 10.96 kg, 11.01 kg and 10.99 kg, respectively. Based on the axiomatic design theory, the emission reduction effects are analyzed from the three aspects of energy structure optimization, production technology improvement and production material selection. The promotion of solar energy in production and operation in the mixing plant, and the application of hydrogen energy in vehicles in reducing energy consumption are quantitatively analyzed. The emission reduction benefits of warm mix technology, material storage and transport technology, the selection of high-quality aggregates, and the application of RAP materials are calculated. It provides ideas for carbon reduction in asphalt pavement construction and low-carbon operation of mixing plant.